2015
DOI: 10.1089/hum.2015.125
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and preliminary clinical evaluation of genetically transduced dermal tissue implants for the sustained secretion of erythropoietin and interferon α

Abstract: Protein drugs are currently delivered by bolus injection and although treatment frequently is successful, these methods also have major drawbacks, which call for the development of alternative technologies allowing prolonged delivery of these drugs. We developed a new ex vivo gene therapy platform called Transduced Autologous Restorative Gene Therapy (TARGT) for sustained long term production and secretion of autologous therapeutic proteins. A biopsy of dermal tissue taken from the patient is transduced ex viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This notion, however, should be tested in controlled clinical studies. Indeed, clinical studies using TARGT tissues secreting erythropoietin in patients with anemia demonstrated safety and efficacy, as indicated by an elevated hematocrit and erythrocyte differentiation similar to multiple bolus injections with recombinant erythropoietin …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This notion, however, should be tested in controlled clinical studies. Indeed, clinical studies using TARGT tissues secreting erythropoietin in patients with anemia demonstrated safety and efficacy, as indicated by an elevated hematocrit and erythrocyte differentiation similar to multiple bolus injections with recombinant erythropoietin …”
Section: Discussionmentioning
confidence: 99%
“…DNA encoding the adalimumab light and heavy chains was inserted into the same open reading frame in the previously described HDAd‐MAR‐EF1α cassette in HD adenovirus DNA (Figure ). The IgG DNA coding sequences were codon optimized and all CpG sequences in the expression cassette were changed, without affecting the gene reading frame.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations